Social Commerce of Indian Customers : Role of Social Media Usage - Siji, Smitha (Indian Journal of Marketing, 2021)
Time spent by users on social or digital media is greatly influenced by the avenues available on social media to engage the users. Social commerce constructs happen to be such avenues. Social commerce constructs influence social media usage, which, in turn, influences the purchase of products online. In this context, the role of social media usage on online purchase intentions was examined in this paper. Though there are many studies on various factors influencing online purchase intentions, this paper focused on finding the impact of social commerce and social media usage on online purchase intentions. Questionnaires were sent to 500 respondents, who were social media users covering different parts of India. Their use of social media and social commerce constructs such as recommendations, ratings and forums, and their impact on online purchase intentions were measured. The results of multiple regression showed that social commerce constructs and social media usage had a positive effect on online purchase intentions. Thus, based on the research findings, it was suggested that companies should use social media platforms to engage their customers in such a way that they are online for a longer duration. However, this would have a social implication as people who spend more time on social media must be aware that their impulse purchases might go up.